Diversity and growth - Gradstein, Mark; Justman, Moshe (Bonn, 2018)
"The diversity of social interaction within economic communities affects productivity and growth, and is itself shaped by economic conditions. These reciprocal effects raise the possibility of multiple equilibria, of setting a socially polarized economy stagnating in poverty on a new path of social integration and economic growth through external intervention or an internal political initiative. This paper describes a simple analytical model that captures these reciprocal effects, and sheds light on the role of government capacity, community leadership, federation and external credit or aid, in achieving economic growth through social integration."